Collecting and collections in times of war or political and social change : COMCOL Annual Conference, Celje 2014 - Hudales, Jože; Roženbergar Šega, Tanja (Zupaničeva knjižnica, 2017)
"The proceedings from Celje conference, we gather in this book, are focused on the importance of mutual dependence within the triangle formed by ideology, the mission of museum collections and types of collections. Changes in ideological perspectives influence the formation and development of collections, and museums' missions are shaped and adapted in line with socio-political development and the related changes."